Behind Every High Earning Man Is a Conscientious Woman: A Study of the Impact of Spousal Personality on Wages - Susan L. Averett; Cynthia Bansak; Julie K. Smith (Institute of Labor Economics (IZA), 2018)
This paper explores the effects of a spouse's personality on earnings. We build on the growing literature spanning economics and psychology that investigates how personality traits affect one's own individual earnings. In particular, several of the big five personality characteristics (extraversion, agreeableness, conscientiousness, neuroticism and openness) have been shown to be predictors of own earnings. To our knowledge only one paper studies the relationship between spousal personality and labor market outcomes finding a strong correlation between the two. We extend this work to assess the linkage between spousal personality and earnings while accounting for the potential endogeneity of the selection into marriage. Using the Household, Income and Labor Dynamics in Australia Survey from 2001â exteuro 2013, we test which spousal personality characteristics affect earnings. Our results indicate that for men, having a conscientious wife raises his earnings while there is little consistent effect of husband's personality on his wife's earnings.
Keywords: J12; J24; J31; 330; conscientiousness; Five Factor Model; HILDA; earnings; personality; marriage; assortative mating